Uma prática discursiva da mentira: sexualidade, moral e verdade em fake news checadas pelo site E-farsas - Silva Júnior, Joseeldo Pereira da (2020)
Present in the daily lives of Brazilians, fake news, as it was conventionally called after the popularization of the term due to the election of the President of the United States Donald Trump, has proved to be a serious social problem, given that its dissemination in social media has contributed to disinformation and influenced, for example, electoral elections. Thinking about it, our main objective in this dissertation was to analyze the fake news produced on the sexuality theme checked by the website E-farces in order to highlight the knowledge-power techniques that constitute them. We also tried to investigate the conditions for the appearance of fake news as a strategy of knowledge / power; analyze how the phenomenon of post-truth implies the spread of fake news in real games about sexuality; investigate fake news, within the scope of journalistic discursive practice, reproduced on the E-farces website, from the perspective of the will to truth procedure; and, finally, to trace a genealogy of urban lies disseminated in France to virtual lies manufactured and shared on social media. As a research problem, we seek to know how fake news articulates with Christian morality to discursivize the field of sexuality. In relation to methodology, our research is affiliated with Foucault's Discursive Studies, based on the basic notions of truth, power and morals, originated from the “archeogeneological method”, constituted from the ideas of the French philosopher Michel Foucault. Our analyzes, in addition to being based on these notions, are also guided by the categories of utterance, discourse and sexuality. This research is characterized for being descriptive-interpretative, of qualitative nature. For the constitution of our corpus, we used the principle of regularity, since, given the extensive number of fake news, the themes of sexuality and religiosity, and sexuality and education appeared with greater recurrence, thus constituting two enunciative series. Thus, we analyzed five news items verified by E-farces, considering the enunciative series proposed. The final analysis reveals that in fake news there is a Christian moral discourse that permeates them, as well as an entrepreneurship in disqualifying the debate about the agenda of sexuality in the Brazilian scenario, especially in the school context, by supporting the “gender ideology” as an instrument political. A conservative movement with the purpose of defending the family and childhood, by extension, has been seen in the political framework of Brazil today, which requires, for this, the spread of fake news as an element of power.